Intervenção com crianças pré-escolares agressivas: suporte à escola e à família em ambiente natural. - Ormeño, Gabriela Isabel Reyes (2004)
Children s aggressive behaviors are related to the multiple contexts of their lives, such as the say the family, school and other social institutions. This study had the aim of evaluating an early intervention program with aggressive pre-school children, involving parents and pre-school teachers in order to improve a reduction on the level of aggressive behaviors, as well as increasing adaptive ones. Three male to sixyear old children, their mothers and school teachers participated of the study. Initially observations of the aggressive behavior of the children were done at school with the aid of a protocol of observation and recording of aggressive behavior. An initial interview with mothers and teachers were also done. The intervention with the children consisted in two sessions of 45 minutes each per week throughout six months, in which topics like: rules impositions, alternative ways to aggressive responses and conflict resolution were discussed. These skills were taught using games, exercises and role-play. The intervention with the mothers occurred once a week and had the goal of capacitating them in terms of managing the behaviors of their children, increasing positive interactions as well as optimizing their support systems and decreasing stressors In regards. to the teachers, there was one 45 minute meeting at school during the Physical Education classes with the purpose of helping them to deal with aggressive situations of their students. The procedure involved a multiple-base-line among participants. Results showed that the children decreased their aggressive behavior in a significant way using alternative behavior to meet their needs. The mothers pointed out that the intervention was useful, improving the quality among their interpersonal relations, especially with their children. The teachers reported that the researcher had established a differential procedure in regards to the children, and this lowered aggressions in their presence. One of the contributions of this study was to demonstrate the effectiveness of an early intervention program with aggressive children; nevertheless the program had little generalization to the classroom. It would be important that future studies focus on the teacher-student as well as children-family interactions.